2002
DOI: 10.1074/jbc.c100603200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for H-NS-mediated Trapping of RNA Polymerase in the Open Initiation Complex at the rrnB P1

Abstract: The Escherichia coli H-NS protein is a nucleoid-associated protein involved in both transcription regulation and DNA compaction. Each of these processes involves H-NS-mediated bridge formation between adjacent DNA helices. With respect to transcription regulation, preferential binding sites in the promoter regions of different genes have been reported, and generally these regions are curved. Often H-NS binding sites overlap with promoter core regions or with binding sites of other regulatory factors. Not in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 50 publications
3
141
2
Order By: Relevance
“…3 A, B). The structure and proposed mode of interaction with DNA provides a rationale for data on the nucleation (28,29) and bridging (24, 30) models of gene repression by H-NS and is consistent with biophysical studies (31) as well as imaging of H-NS: DNA nucleoprotein complexes by atomic force microscopy and electron microscopy (23,32,33). Small angle X-ray scattering (SAXS) analysis showed that at 10°C and 0.3-0.4 mM H-NS 1-83 adopts a conformation in solution that is comparable to the oligomer present in the crystal; under these conditions extending to an average of eight monomers or four dimeric units (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…3 A, B). The structure and proposed mode of interaction with DNA provides a rationale for data on the nucleation (28,29) and bridging (24, 30) models of gene repression by H-NS and is consistent with biophysical studies (31) as well as imaging of H-NS: DNA nucleoprotein complexes by atomic force microscopy and electron microscopy (23,32,33). Small angle X-ray scattering (SAXS) analysis showed that at 10°C and 0.3-0.4 mM H-NS 1-83 adopts a conformation in solution that is comparable to the oligomer present in the crystal; under these conditions extending to an average of eight monomers or four dimeric units (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…H-NS exists primarily as a dimer at low concentrations but can multimerize into higher order complexes [4,5] that form bridges between adjacent DNA helices [6]. Optical tweezers have been used to demonstrate that H-NS dimers or multimers can simultaneously interact with separate DNA binding sites [7••].…”
Section: H-ns--a Nucleoid Proteinmentioning
confidence: 99%
“…Regulatory effects of supercoiling are linked to metabolic and environmental conditions. Thus, H-NS has been viewed as a nucleoid structuring protein with global effects on gene expression [3].H-NS exists primarily as a dimer at low concentrations but can multimerize into higher order complexes [4,5] that form bridges between adjacent DNA helices [6]. Optical tweezers have been used to demonstrate that H-NS dimers or multimers can simultaneously interact with separate DNA binding sites [7••].…”
mentioning
confidence: 99%
“…In addition to RNAP, three transcription factors have been reported to bind site-specifically to the E. coli rRNA promoter region, Fis, Lrp, and H-NS (Ross et al 1990;Hirvonen et al 2001;Dame et al 2002;Pul et al 2007). Each has been reported to influence chromosome structure (Skoko et al 2006;Bouffartigues et al 2007;Hadizadeh et al 2012), making these factors candidates for contributors to rRNA operon colocalization.…”
Section: (C) Oric Rrnc (Rlg11999) (D) Rrnb Oric (Rlg7440) (E) λAtmentioning
confidence: 99%